A First Generation Fusion Reactor Using the D-3He Cycle. (3rd April 2021) - Mazzucato, E.
Abstract: With the goal of reducing the radiation damage and radioactive waste that will occur in a tokamak reactor using the deuterium-tritium cycle, this paper proposes a new magnetic scheme capable of confining hot and dense deuterium–helium3 plasmas. It consists of two 200-m-long cylindrical plasmas connected by semicircular sections to form a racetrack configuration. The reactor should be capable of producing from 7.8 to 13 GW of fusion power when operating at electron densities of 2 × 10 20  m −3, temperature 40 keV, and density ratios of the two reactants from 1:2 to 2:1.